System Review of the Efficacy of Acupuncture on Hemiplegic Gait in Stroke Patients - Meiqin LIN; Weilin LIU (康复学报)
Objective:In order to obtain objective evidence of acupuncture therapy for stroke patients with hemiplegic gait, we would collect the published studies, and systematic review of the quality, providing reliable evidence for clinical application.Methods:Computer comprehensively searched Pubmed, EMbase, the Cochrane library, Web of Science, Chinese Science and Technology Database, Wanfang, China National Knowledge Infrastructure, Chinese Biology Medicine and Traditional Chinese Medicine Database. According to bias risk assessment tool of Cochrane, assessed the quality of the studies, evaluated the quality of each study, ReMan 5.2 software was used for meta-analysis and statistical appraisal of effect size.Results:Participants included 22 studies (n=1, 519), 8 of randomized controlled trials (RCT), 14 of controlled clinical trials (CCT). The results suggested that the lower limb Fugl-Meyer assessment scale: at the acute stage which is WMD=6.71, 95%CI (5.51, 5.72) and P<0.000, 01; at the restoration stage which is WMD=2.50, 95%CI (1.49, 3.50) and P<0.000, 01; at the sequela stage only 1 trial that has statistical significance (P=0.003); three trials were aimed at the treatment of post stroke spasm (any course), which is WMD=1.60, 95%CI (0.92, 2.28) and P<0.000, 01. Acupuncture could improve time-distance parameters, but reported inconsistent results, improve the kinematic parameters of the hip, knee and ankle joint and enhance EMG of back extensor, slow spasm of limbs, increase the balance and walking function, improve the ability of daily life in stroke patients through analysis of quantitative gait.Conclusion:The existing evidences suggested that acupuncture treatment could improve time-distance and kinematic parameters of lower limbs, suppress spasm and increase balance in stroke patients. But the trials involved are low quality, therefore, which remains need to design more rigorous randomized controlled trial to further verification.